Diagnosis Radiologis Enterocolitis Necroticans - Soeroyo Soeroyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
Necrotizing enterocolitis (NEC) is a multifactorial disease with an unknown pathogenesis. NEC has a high Mortality rate and incidence is predominant in premature with stress.NEC shows characteristic signs of the ischemic necrosis of the intestine, which can be detected on X-ray picture.X-ray examination would be more useful for detecting NEC in an early stage, following the pro' cess and for the reopening of the stricture of the intestine.Key Words: necrotizing enterocolitis (NEC) - ischemic necrosis - radiology - neonatology -prematurity